SAFE REUSE OF TREATED WASTEWATER AND SLUDGE IN DECENTRALIZED SYSTEM - Hastuti, Elis; Darwati, Sri; Anggraini, Fitrijani (MATTER: International Journal of Science and Technology, 2019)
The unsafe water and solid reuse from decentralized wastewater treatment plant still occur due to the lack of improved and effective water management. This paper has aims to provide research findings of main management aspect of decentralized wastewater treatment plant with water reuse orientation. The scope of analysis includes wastewater treatment process performance evaluation, health risk, water reuse constraints and community motivation. The decentralized wastewater system had been designed as green technology in some settlements areas, which have low maintenance, low sludge production, and have high potential of water reuse for non potable water demand. According to the treatment schemes for water reuse system, the management is affected by treatment performance, proper maintenance, environmental condition and community motivation. The treated water quality according to water reuse standard of USEPA can be a source for agriculture or non-potable water demand and reduce contamination of water sources. Achievement of the effective wastewater management system could provide non-potable water source to fulfill 50-65% of clean water demand according water reuse standards. There are some constraints of wastewater reuse that were minimized through some steps to enhance wastewater system towards safe water and solid reuse.